2008
DOI: 10.1002/ps.1604
|View full text |Cite
|
Sign up to set email alerts
|

Responses to clomazone and 5‐ketoclomazone by Echinochloa phyllopogon resistant to multiple herbicides in Californian rice fields

Abstract: Cross-resistance to clomazone explains failures to control R plants in rice fields, and safening by P450 inhibitors suggests that oxidative activation of clomazone is needed for toxicity to E. phyllopogon. Clomazone resistance requires mitigation of 5-ketoclomazone toxicity, but P450 detoxification may not significantly confer resistance, as P450 inhibitors poorly synergized 5-ketoclopmazone in R plants. Responses to paraquat suggest research on mechanisms to mitigate photooxidation in R and S plants is needed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 34 publications
5
63
1
4
Order By: Relevance
“…Ratios of the GR 50 (herbicide dose to inhibit growth by 50%) values of resistant to susceptible E. phyllopogon plants of approximately 2 indicated low levels of clomazone resistance (Yasuor et al, 2008). This resistance was not caused by differential uptake, translocation, or bioactivation of inactive clomazone to active 5-ketoclomazone (Yasuor et al, 2008). Based on inhibitor data, Fischer et al (2000b) suggested that herbicide degradation mediated by cytochrome P450 monooxygenases (EC 1.14.14.1 [P450]) was a mechanism conferring E. phyllopogon resistance to multiple herbicides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ratios of the GR 50 (herbicide dose to inhibit growth by 50%) values of resistant to susceptible E. phyllopogon plants of approximately 2 indicated low levels of clomazone resistance (Yasuor et al, 2008). This resistance was not caused by differential uptake, translocation, or bioactivation of inactive clomazone to active 5-ketoclomazone (Yasuor et al, 2008). Based on inhibitor data, Fischer et al (2000b) suggested that herbicide degradation mediated by cytochrome P450 monooxygenases (EC 1.14.14.1 [P450]) was a mechanism conferring E. phyllopogon resistance to multiple herbicides.…”
mentioning
confidence: 99%
“…These include the lipid synthesis inhibitors molinate and thiobencarb; the acetyl-CoA carboxylase inhibitors fenoxapropethyl and cyhalofop; the acetolactate synthase inhibitors bispyribac-sodium, bensulfuron-methyl, and penoxsulam; and the DXP synthase inhibitor clomazone (Fischer et al, 2000a;Yasuor et al, 2008Yasuor et al, , 2009). Ratios of the GR 50 (herbicide dose to inhibit growth by 50%) values of resistant to susceptible E. phyllopogon plants of approximately 2 indicated low levels of clomazone resistance (Yasuor et al, 2008). This resistance was not caused by differential uptake, translocation, or bioactivation of inactive clomazone to active 5-ketoclomazone (Yasuor et al, 2008).…”
mentioning
confidence: 99%
“…Further complicating the situation in rice, populations of late watergrass and barnyardgrass (Echinochloa crus-galli) with resistance to both ACCase inhibitors and thiocarbamates, and thus exhibiting multiple resistance, were reported in 2000. Later research confirmed that the mechanisms of multiple resistance to several herbicide classes are due to metabolic degradation of these compounds (Yasuor et al 2008(Yasuor et al , 2009.…”
Section: Herbicide Resistance In Californiamentioning
confidence: 93%
“…米国カリフォルニア州で発見された除草剤抵抗性タイヌビ エ(Echinochloa phyllopogon = E. oryzicola)は,異なる作用 機構の除草剤に抵抗性を示す多剤抵抗性型であることが知ら れていた(Fischer et al 2000;Osuna et al 2002;Ruiz-Santaella et al 2006;Bakkali et al 2007;Yasuor et al 2008Yasuor et al , 2009 …”
Section: .タイヌビエの非作用点抵抗性unclassified